Impact of organizational decentralization degree on job satisfaction and job performance: a hierarchical linear model analysis for construction projects. Issue 4 (29th April 2021) - Sun, Jun; Wang, Cynthia Changxin; Yang, Zhiling; Yu, Tianshu; Li, Jintao; Xiong, Xiaoqian
Abstract : Purpose: Modern construction projects are increasingly complex and rely heavily on multi-discipline collaboration, and this leads to a more and more decentralized project-based structure widely adopted in the construction industry. While job satisfaction (JS) and job performance (JP) have been heavily studied previously, few considered the impact of organizational structure and none investigated the relationship between the organizational decentralization degree with JS and JP. This research aims to fill this research gap and investigate the impacts of organizational decentralization degree on JS and JP and facilitate a better project management practice for large-scale construction projects. Design/methodology/approach: This research firstly establishes four hypotheses based on the literature review on general project-based organizations, then the hypotheses are tested by a survey covering 25 large complex construction projects in China. A hierarchical linear model analysis was carried out to analyze the survey data and to study the relationships between organizational decentralization degree, job satisfaction and job performance. Findings: Analysis results show that projects' employees' JS and JP are positively correlated with the construction project organizations' decentralization degree, respectively. The decentralization degree has a higher impact on JS than on JP. Employees' JP is positively correlated with their JS, and a higher decentralization degree leads to a more significant positive impact that JS puts on JP. Originality/value: The findings are new evidence of how construction organization structure and its decentralization degree can affect project employees' JS and JP. This research provides valuable guidance for the industry's management practice and is particularly important for large, complex and highly decentralized construction projects.